2008
DOI: 10.1002/arch.20227
|View full text |Cite
|
Sign up to set email alerts
|

Prophenoloxidases 1 and 2 from the spruce budworm, Choristoneura fumiferana: Molecular cloning and assessment of transcriptional regulation by a polydnavirus

Abstract: Immune challenge in arthropods is frequently accompanied by melanization of the hemolymph, a reaction triggered by the activation of prophenoloxidase (PPO). Because their immature stages are spent inside the hemocoel of insect larvae, endoparasitoids have evolved strategies to escape or counter melanin formation. Very little molecular information is available on these endoparasitoid counterstrategies. We have sought to shed light on the inhibition of melanization in the spruce budworm, Choristoneura fumiferana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
5
11
0
Order By: Relevance
“…Our results suggest that the transcription or translation of proPO and MasSPH can be altered by parasitization. Studies on other parasitoid-host systems have found that the transcription of melanization-related genes such as proPO, serine proteases, and serpins is regulated by parasitization (Wertheim et al, 2005;Doucet et al, 2008). In accordance with these studies, we found that the expressions of proPO and MasSPH were altered following parasitization, suggesting that disruption of melanization would be a way for P. puparum to modulate P. xuthus immune reaction.…”
Section: Humoral Immune Proteinssupporting
confidence: 88%
See 1 more Smart Citation
“…Our results suggest that the transcription or translation of proPO and MasSPH can be altered by parasitization. Studies on other parasitoid-host systems have found that the transcription of melanization-related genes such as proPO, serine proteases, and serpins is regulated by parasitization (Wertheim et al, 2005;Doucet et al, 2008). In accordance with these studies, we found that the expressions of proPO and MasSPH were altered following parasitization, suggesting that disruption of melanization would be a way for P. puparum to modulate P. xuthus immune reaction.…”
Section: Humoral Immune Proteinssupporting
confidence: 88%
“…As a key defense mechanism against intruding organisms, melanization is the result of the proPO activation cascade regulated by serine proteinases, which leads to the formation of melanin and other toxic phenolic compounds (Ashida and Brey, 1998;Vass and Nappi, 2000). Among the known mechanisms to fend off parasitoid, defensive melanization is perhaps the most ubiquitous and best characterized among humoral response (Doucet et al, 2008). Thus a reduced melanization caused by the inhibition of phenoloxidase (PO) activity and proPO-activating enzyme serine protease (PPAE) is often observed of parasitization (Lavine and Beckage, 1995;Asgari, 2006).…”
Section: Humoral Immune Proteinsmentioning
confidence: 99%
“…This is similar to results from previous studies of H. cunea (Park et al 1997), H. virescens (Shelby and Popham 2008), and C. fumiferana (Doucet et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…In A. subalbatus at least five distinct PPOs have been identified and the genomes of Drosophila melanogaster and Manduca sexta have three PO genes. However, only two cDNAs encoding PPOs have been reported in most of other lepidopteran insects, for example Hyphantria cunea (Park et al 1997), B. mori (Asano and Ashida 2001), H. virescens (Shelby and Popham 2008) and C. fumiferana (Doucet et al 2008). In our study, by using native-PAGE and coloration with standard substrate L-dopa, we found that P. xylostella also has two PPO isoenzymes, PxPPO1 and PxPPO2, which was further proved by sequencing of their cDNA.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation